The role of the isolation of the marginal seas during the Pleistocene in the genetic structure of black sea bream Acanthopagrus schlegelii (Bleeker, 1854) in the coastal waters of Japan - Yutaro Yamashita; Gustavo Sanchez; Kentaro Kawai; Satoshi Tomano; Hiroki Fujita; Tetsuya Umino (PeerJ, 2021)
The black sea bream Acanthopagrus schlegelii (Bleeker, 1854) is a commercially important species in Japanese waters. Assessing its population structure is essential to ensure its sustainability. In the Northwestern Pacific, historical glacial and interglacial periods during the Pleistocene have shaped the population structure of many coastal marine fishes. However, whether these events affected the population of black sea bream remains unknown. To test this hypothesis and to assess the population structure of black sea bream, we used 1,046 sequences of the mitochondrial control region from individuals collected throughout almost the entire Japanese coastal waters and combined them with 118 sequences from populations distributed in other marginal seas of the Northwestern Pacific Ocean. As in other coastal marine fish with similar distribution, we also found evidence that the glacial refugia on the marginal seas prompted the formation of three lineages in black sea bream. These lineages present signatures of population growth that coincided with the interglacial periods of the Pleistocene. While the origin of Lineages B and C remains unclear, the higher relative frequency of Lineage A in the southernmost location suggests its origin in the South China Sea. The non-significant pairwise ΦST and AMOVA of Japanese populations and the presence of these three lineages mixed in Japanese waters; strongly suggest that these lineages are homogenized in both the Sea of Japan and the Pacific Ocean. Our results indicate that the black sea bream should be managed as a single stock in Japan until the strength of connectivity in contemporary populations is further addressed using non-coding nuclear markers.